2021
DOI: 10.1073/pnas.2111046118
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment-mediated cancer dormancy: Insights from metastability theory

Abstract: Dormancy is an evolutionarily conserved protective mechanism widely observed in nature. A pathological example is found during cancer metastasis, where cancer cells disseminate from the primary tumor, home to secondary organs, and enter a growth-arrested state, which could last for decades. Recent studies have pointed toward the microenvironment being heavily involved in inducing, preserving, or ceasing this dormant state, with a strong focus on identifying specific molecular mechanisms and signaling pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 111 publications
0
16
0
Order By: Relevance
“…The TME has been shown to be crucial for tumor dormancy initiation and maintenance in breast cancer cells ( Bakhshandeh et al, 2022 ) via paracrine/niche-related signaling [e.g., bone morphogenetic protein (BMP) 4 and 7 ( Kobayashi et al, 2011 ; Gao et al, 2012 ), TGF-β2 ( Bragado et al, 2013 ) and type 3 collagen ( Di Martino et al, 2022 )] that can maintain cancer cell dormancy in experimental models. In the BM as the most studied sanctuary for DTCs, three supporting niches have been described.…”
Section: Micrometastatic Disease and Dormancy In Breast Cancermentioning
confidence: 99%
“…The TME has been shown to be crucial for tumor dormancy initiation and maintenance in breast cancer cells ( Bakhshandeh et al, 2022 ) via paracrine/niche-related signaling [e.g., bone morphogenetic protein (BMP) 4 and 7 ( Kobayashi et al, 2011 ; Gao et al, 2012 ), TGF-β2 ( Bragado et al, 2013 ) and type 3 collagen ( Di Martino et al, 2022 )] that can maintain cancer cell dormancy in experimental models. In the BM as the most studied sanctuary for DTCs, three supporting niches have been described.…”
Section: Micrometastatic Disease and Dormancy In Breast Cancermentioning
confidence: 99%
“…Cancer progression is dependent on the capacity of tumor cells to establish a supportive TME ( 14 ). Studies have demonstrated that the microenvironment is involved in causing a condition of growth arrest in the tumor ( 15 ). At the same time, tumors fight against the normal microenvironment to overcome the anti-tumor pressure ( 15 ).…”
Section: The Tme Of Crcmentioning
confidence: 99%
“…Studies have demonstrated that the microenvironment is involved in causing a condition of growth arrest in the tumor ( 15 ). At the same time, tumors fight against the normal microenvironment to overcome the anti-tumor pressure ( 15 ). While tumors communicate closely with the surrounding microenvironment, the biochemical signals in the microenvironment impact cell growth and tumorigenesis ( 16 , 17 ).…”
Section: The Tme Of Crcmentioning
confidence: 99%
“…The interactions between the dysfunctional tissues and nutrients can then start a destructive cycle of overnutrition and oxidative stress [ 134 , 135 ]. In addition, oxidative stress also triggers tumor cell dormancy [ 136 ] and autophagy to prevent cell apoptosis [ 137 ], which promotes the survival of dormant cancer cells and increases the chances of metastatic tumor recurrence [ 138 ].…”
Section: Ecm Stiffening Reprograms Cancer Cell Metabolism Leading To ...mentioning
confidence: 99%